Entrepreneurial orientation and effects on firm performance on SMEs in Sabah manufacturing Sector / Melvin Mojikon, Azizan Abdullah and Sofian Shamsuddin - Mojikon, Melvin; Abdullah, Azizan; Shamsuddin, Sofian (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
Entrepreneurial Orientation (EO) has been defined as the strategic orientation, which employed by firms in order to identify ways and creating a specific set of methods through the assistance of various decision making, since numerous ways and practices of entrepreneurial aspects were eventually realized. Hence, this study was conducted based on the phenomenon experienced by a number of manufacturing firms in the State of Sabah, Malaysia, within the context of Small and Medium-Sized Enterprises (SMEs). The EO, moreover, was deemed as a multidimensional construct encompassing two dimensions, namely autonomy and innovativeness. This study employed a quantitative approach as for methodology. In this study, proportionate stratified random sampling was applied. The location of this study involved the area of West Coast Division in the State of Sabah. Meanwhile, the samples were consisted of 175 responses among selected owners and managers of small and medium-sized manufacturing firms. The data analysis was carried out through Partial Least Squares-Structural Equation Modeling (PLS-SEM) techniques by using the SmartPLS 2.0 M3 software. Based on the attributes of EO consisting of autonomy and innovativeness, the results were statistically demonstrated their significant relationships with firm performance. Furthermore, the factor of the government, which plays an important role, as the moderator, was proven a significant in the relationship between autonomy and firm performance, whilst, portrayed an insignificant and non-influential in strengthening the relationships between other EO dimension (i.e. innovativeness) and firm performance.